The secret of a heart note - Lee, Stacey (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2016)
An aroma expert embarks on what she fears will be a life of solitude and dreams of a normal high school existence before an accident leads to an unexpected forbidden romance.